[Immaculate Conception in San Juan Nuevo] - Maria Campoverde::::::photographer::: (2005)
Description supplied by photographer: 'Una foto de la Inmaculada Concepción tomada desde la capilla en San Juan Nuevo.' - 'A photo of the Immaculate Conception in San Juan Nuevo.'